A carbon black reinforced modified fluororubber composition with low compression set and a method for preparing the same

CN122978616APending Publication Date: 2026-10-27WENZHOU BANGXINYUAN TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611129211.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,氟橡胶存在两大固有缺陷:一是压缩永久变形(以下简称"压变")较大,特别是在200℃以上长期使用后,密封力快速衰减导致泄漏;二是耐磨性不足,在动态往复或旋转密封工况下易磨损失效

Benefits of technology

(1)本发明通过白炭黑与低结构炭黑N990以特定比例(白炭黑:炭黑 = 1.5-15:1)复配,利用N990炭黑石墨微晶尺寸大、结构有序度高的特点,与白炭黑产生协同效应,在不牺牲力学性能的前提下,将氟橡胶在200℃×70h条件下的压缩永久变形从传统配方的38.1%显著降低至19%左右,降幅达50%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978616A_ABST
    Figure CN122978616A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of high polymer materials, in particular to a carbon black reinforced modified fluororubber composition with low compression set and a preparation method thereof.The composition comprises the following components by weight: 100 parts of fluororubber; 10-30 parts of white carbon black; 2-15 parts of carbon black; 1-3 parts of vulcanizing agent; 1-3 parts of accelerator; 1-3 parts of release agent; and the carbon black is N990 carbon black.The present application uses white carbon black and low-structure carbon black N990 in a specific ratio, and utilizes the characteristics of large graphite microcrystal size and high structure order degree of N990 carbon black to produce a synergistic effect with white carbon black, thereby significantly reducing the compression set of fluororubber under the condition of 200 DEG C x 70 h without sacrificing mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, specifically to a carbon black-reinforced modified fluororubber composition with low compression set and its preparation method, which is particularly suitable for high-temperature dynamic seals. Background Technology

[0002] Fluororubber (FKM) is widely used in sealing products for harsh environments such as aerospace and semiconductors due to its excellent resistance to high temperatures, oil, and chemical media. However, fluororubber has two inherent drawbacks: first, it has a large compression set, especially after long-term use at temperatures above 200°C, which causes the sealing force to decay rapidly, leading to leakage; second, it has insufficient wear resistance and is prone to wear failure under dynamic reciprocating or rotating sealing conditions.

[0003] To reduce compression set, existing technologies mainly employ the following methods: (1) Improved vulcanization system – The traditional bisphenol AF vulcanization system is replaced with a peroxide vulcanization system. Although the compression set of peroxide vulcanized fluororubber has been improved, it is still difficult to meet the requirements of high-end seals (compression set ≤20%).

[0004] (2) Filler improvement - Adding silica can reduce compression set, but it will significantly reduce tensile strength and abrasion resistance; adding reinforcing carbon black (such as N990) can improve strength, but it has limited improvement on compression set, or even worsens it. This is because carbon black filler is traditionally believed to increase the hysteresis heat generation of rubber, which is not conducive to elastic recovery.

[0005] (3) Chinese patent CN110229446A discloses a fluororubber for vacuum drying jar, which is compounded with 25-35 parts of N990 carbon black and 15-25 parts of white carbon black. However, it uses a bisphenol AF vulcanization system and has a high amount of carbon black. It does not specifically solve the problem of compression set under high temperature (200℃×70h) conditions.

[0006] In summary, the prior art has not yet provided a fluororubber composition that can achieve low compression set while maintaining the mechanical performance requirements of the fluororubber for the seal, and at the same time take into account good wear resistance. Summary of the Invention

[0007] To address the shortcomings of existing technologies, this application provides a carbon black-reinforced modified fluororubber composition with low compression set and its preparation method.

[0008] To achieve the above objectives, the technical solution of this application is as follows: a carbon black-reinforced modified fluororubber composition with low compression set, comprising the following components in parts by weight: 100 parts by weight of fluororubber; 10-30 parts by weight of silica; 2-15 parts by weight of carbon black; 1-3 parts by weight of vulcanizing agent; 1-3 parts by weight of accelerator; 1-3 parts by weight of release agent; wherein the carbon black is N990 carbon black.

[0009] Furthermore, the precipitated silica is 15-25 parts by weight, and the carbon black is 2-5 parts by weight.

[0010] Furthermore, it includes the following components in parts by weight: 100 parts fluororubber; 25 parts silica; 2 parts carbon black; 2 parts accelerator; 2 parts vulcanizing agent; and 1 part mold release agent.

[0011] Furthermore, the fluororubber is a peroxide-based fluororubber and / or a triazine-based fluororubber.

[0012] Furthermore, the release agent is struktol WS280 and / or struktol HT290.

[0013] Furthermore, the silica is hydrophobically modified silica and / or hydrophilically modified silica.

[0014] Furthermore, the weight ratio of the silica to the carbon black is (1.5-15):1.

[0015] Furthermore, the promoter is at least one of BPP, TAIC, and BTPPC.

[0016] Furthermore, the vulcanizing agent is at least one of bis(2,5-diphenyltriazine)-tetrabutylammonium salt and BOAP.

[0017] A method for preparing the composition as described above includes the following steps: (1) Weigh the raw materials according to the formula requirements; (2) Add the raw materials from step (1) into a two-roll mill and mix them at a temperature of 35-75℃ until they are uniformly mixed to obtain a compound. (3) The compound obtained in step (2) is vulcanized in a vulcanizing machine for a period of time. The vulcanization temperature is 155-190℃ and the vulcanization time is 8-12min. (4) Place the material obtained by vulcanization in step (3) in a blower oven for two-stage vulcanization. The vulcanization temperature is 185-215℃ and the vulcanization time is 24h.

[0018] Furthermore, in step (2), the initial smelting temperature is 50℃; in step (3), the first-stage vulcanization temperature is 170℃ and the vulcanization time is 10min; in step (4), the second-stage vulcanization temperature is 200℃.

[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention uses a specific ratio of silica and low-structure carbon black N990 (silica:carbon black = 1.5-15:1) to compound N990 carbon black. The large size and high degree of structural order of graphite microcrystals of N990 carbon black produce a synergistic effect with silica. Without sacrificing mechanical properties, the compression set of fluororubber under 200℃×70h conditions is significantly reduced from 38.1% in the traditional formula to about 19%, a reduction of 50%.

[0020] (2) Compared with traditional reinforcing carbon black N330, the wear amount of the N990 compound scheme of the present invention is reduced from 106.9 mm³ to 75.3-78.1 mm³, and the wear resistance is significantly improved. At the same time, cross-sectional SEM shows that the filler is evenly dispersed and exhibits ductile fracture characteristics, avoiding stress concentration and increased permanent deformation caused by filler agglomeration or interface defects.

[0021] (3) Systematic characterization by IR, XRD, SEM and other methods proved that the key mechanism of reducing compression set in this invention lies in the graphite microcrystalline structure of N990 carbon black (rather than surface chemical modification), excluding interference from other factors. Infrared spectra showed that there was no substantial difference in the types and contents of functional groups on the surface of different carbon blacks (140R, N990, N330), while XRD showed that N990 had the sharpest (002) diffraction peak and the smallest half-width, reflecting its larger graphite microcrystalline size and higher structural order.

[0022] (4) The composition prepared in the embodiments of the present invention has a hardness of 70-85 Shore A (which is higher than the original formula of 69 Shore A and is more suitable for high pressure sealing) and a tensile strength of ≥8 MPa, which fully meets the requirements for use of high temperature dynamic seals. Attached Figure Description

[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, obtaining other drawings based on these drawings without creative effort still falls within the scope of the present invention.

[0024] Figure 1The images are scanning electron microscope (SEM) images of the samples obtained in Examples 1-2 and Comparative Examples 1-2, where (a) is sample C1 (140R), (b) is sample C2 (N990 / low silica), (c) is sample C3 (N990 / high silica), and (d) is sample C4 (N330). Figure 2 The infrared (IR) spectra of the samples obtained in Examples 1-2 and Comparative Examples 1-2 are shown below. Figure 3 X-ray diffraction (XRD) patterns of carbon black 140R (C1), silica R972 (C2), carbon black N990 (C3), and carbon black N330 (C4); Figure 4 Comparison of compression set of samples obtained in Examples 1-2 and Comparative Examples 1-2 (200℃×70h, ASTM D395 Method B). Figure 5 Stress-strain curves (ASTM D412) of the samples obtained in Examples 1-2 and Comparative Examples 1-2. Figure 6 This is a comparison chart of the hardness of the samples obtained in Examples 1-2 and Comparative Examples 1-2 (ASTM D2240). Figure 7 Vulcanization curves (RPA2000) of the samples obtained in Examples 1-2 and Comparative Examples 1-2. Figure 8 The thermogravimetric analysis (TGA) curves of the samples obtained in Examples 1-2 and Comparative Examples 1-2 are shown, where (a) is the TG curve and (b) is the DTG curve. Detailed Implementation

[0025] To make the technical problems, technical solutions, and beneficial effects to be solved by this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and are not intended to limit the scope of this application.

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application. The terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.

[0027] The main raw materials used in the following examples and comparative examples are as follows: Fluororubber raw rubber: Peroxide-based fluororubber P959, fluorine content 67%, Solvay. Reinforcing carbon black: 140R, Degussa; N990, Cancarb; N330, Cabot. Silica: R972 fumed silica, Evonik. Accelerators: TAIC, AkzoNobel Vulcanizing agent: 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, Akzo Release agent: HT290, struktol Comparative Example 1: The preparation of the carbon black-reinforced modified fluororubber composition ① with low compression set is carried out according to the preparation method described in this application, and the steps are as follows: S1. Weigh out 100 parts by weight of fluororubber raw rubber, 2 parts by weight of carbon black 140R, 15 parts by weight of silica R972, 2 parts by weight of accelerator ④ TAIC, 2 parts by weight of vulcanizing agent ⑤ bis(2,5)-5, and 1 part by weight of release agent ⑥ HT290.

[0028] S2. Add the fluororubber raw rubber ① weighed in S1, carbon black ② 140R, silica ③ R972, accelerator ④, vulcanizing agent ⑤, and release agent ⑥ to a two-roll mill and mix them at a two-roll mill temperature of 30-70℃ (preferably 50℃) until they are mixed evenly to obtain compound rubber ⑦.

[0029] S3. The compound obtained in S2 is subjected to a vulcanization process in a vacuum vulcanizing machine at a vulcanization temperature of 170℃ and a vulcanization time of 10min to form a sealing ring and a test piece.

[0030] S4. Place the sealing ring and test piece prepared in S3 into a forced-air drying oven for two-stage vulcanization ⑨. The vulcanization temperature is 200℃ and the vulcanization time is 24h. The resulting sample is recorded as C1.

[0031] Example 1: S1. Weigh out 100 parts by weight of fluororubber, 2 parts by weight of N990, 25 parts by weight of R972, 2 parts by weight of accelerator, 2 parts by weight of vulcanizing agent, and 1 part by weight of release agent.

[0032] S2. Add the rubber weighed in S1, carbon black N990, silica R972, accelerator, vulcanizing agent, and release agent to a two-roll mill for mixing. The mixing temperature is 30-70℃, preferably 50℃, until the mixture is uniform.

[0033] S3. The compound obtained in S2 is vulcanized in a vacuum vulcanizing machine to form sealing rings and test pieces. The vulcanization temperature is 170℃ and the vulcanization time is 10min.

[0034] S4. Place the sealing ring and test piece prepared in S3 in a forced-air drying oven for two-stage vulcanization. The vulcanization temperature is 200℃ and the vulcanization time is 24h. The resulting sample is recorded as C2.

[0035] Example 2: S1. Weigh out 100 parts of fluororubber, 12 parts of N990, 15 parts of R972, 2 parts of accelerator, 2 parts of vulcanizing agent, and 1 part of mold release agent.

[0036] S2. Add the rubber weighed in S1, carbon black N990, silica R972, accelerator, vulcanizing agent, and release agent to a two-roll mill for mixing. The mixing temperature is 30-70℃, preferably 50℃, until the mixture is uniform.

[0037] S3. The compound obtained in S2 is vulcanized in a vacuum vulcanizing machine to form sealing rings and test pieces. The vulcanization temperature is 170℃ and the vulcanization time is 10min.

[0038] S4. Place the sealing ring and test piece prepared in S3 in a forced-air drying oven for two-stage vulcanization. The vulcanization temperature is 200℃ and the vulcanization time is 70h. The resulting sample is recorded as C3.

[0039] Comparative Example 2: S1. Weigh out 100 parts of fluororubber, 12 parts of N330, 15 parts of R972, 2 parts of accelerator, 2 parts of vulcanizing agent, and 1 part of release agent.

[0040] S2. Add the rubber weighed in S1, carbon black N330, silica R972, accelerator, vulcanizing agent, and release agent to a two-roll mill for mixing. The mixing temperature is 30-70℃, preferably 50℃, until the mixture is uniform.

[0041] S3. The compound obtained in S2 is vulcanized in a vacuum vulcanizing machine to form sealing rings and test pieces. The vulcanization temperature is 170℃ and the vulcanization time is 10min.

[0042] S4. Place the sealing ring and test piece prepared in S3 in a forced-air drying oven for two-stage vulcanization. The vulcanization temperature is 200℃ and the vulcanization time is 70h. The resulting sample is recorded as C4.

[0043] The C1-C4 samples prepared in Examples 1-2 and Comparative Examples 1-2 were subjected to the following tests: Scanning electron microscopy (SEM): Thermo Fisher Scientific Nano SEM 200, results are shown below. Figure 1 (a); Infrared spectrum (IR): PerkinElmer L1230104, results are shown in Figure 2 X-ray diffraction (XRD): Bruker D8 ADVANCE, results are shown in [link to results]. Figure 3 The prepared sealing ring and test piece were subjected to performance testing, with compression set measured according to ASTM D395 Method B (200℃ × 70h). The results are shown in [Figure Number]. Figure 4 Tensile properties: ASTM D412, results are shown in [link to results]. Figure 5 Hardness: ASTM D2240, results are shown below. Figure 6 Vulcanization curve: ALPHA RPA2000, results are shown in [link to results]. Figure 7 Thermogravimetric analysis (TGA): Beijing Instrument High-Tech ZSL-V, results are shown in [link to results]. Figure 8 .

[0044] The results are summarized in the table below: from Figure 1 It can be seen that the filler in the low compression set samples (C2, C3) is uniformly dispersed and the cross-section shows ductile fracture characteristics, with no obvious agglomeration or debonding; while the high compression set samples (C1, C4) have local filler agglomeration or interface defects, which leads to stress concentration and increased permanent deformation.

[0045] from Figure 2 It can be seen that the infrared spectra of the four samples are almost completely overlapping, indicating that there is no substantial difference in the types and contents of functional groups on the surface of different carbon blacks (140R, N990, N330). Therefore, it can be inferred that the key to reducing compression set in this invention is not surface chemical modification, but rather the carbon black microcrystalline structure and the synergistic effect of compounding with silica.

[0046] from Figure 3 It can be seen that the (002) diffraction peak of N990 carbon black is the sharpest and has the smallest half-width at half-maximum, reflecting its larger graphite crystallite size and higher structural order. This highly ordered carbon structure allows N990, when blended with silica, to impart lower hysteresis heat generation and better elastic recovery to fluororubber, thereby reducing compression set to about 19%. In contrast, 140R and N330 have broadened peaks and smaller crystallite sizes, which, while providing strong reinforcement, are not conducive to improving compression set.

[0047] from Figure 7 The vulcanization curves show that C2 and C3 (N990 compound) have lower maximum torque (MH) (7.5-9.2 dN·m), which is beneficial for low compression set; C4 (N330 compound) has higher MH (10.8 dN·m), corresponding to poorer compression set performance.

[0048] The original formulation C1 decreased to 38.1% under 200℃×70h, while the modified samples C2 and C3 decreased to 19.1% and 19.5% respectively, a reduction of 50%, which is far superior to the N330 modified sample C4. Wear resistance tests showed that C1 had a wear amount of 71.6 mm³, C2 78.1 mm³, and C3 75.3 mm³, while sample C4 reached a high of 106.9 mm³, indicating that the C2 and C3 blend is significantly superior to the N330 modified sample C4 in terms of wear resistance.

[0049] In terms of mechanics, the modified tensile strength decreased from 14.5 MPa to 8.0~11.5 MPa, but still met the requirements for sealing applications (≥8 MPa). The hardness increased from 69 Shore A to 80 Shore A, making it more suitable for high-pressure sealing.

[0050] In summary, this invention significantly reduces compression set by compounding silica and low-structure carbon black N990 with fluororubber, achieving synergistic optimization of compression set and abrasion resistance of fluororubber.

[0051] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A carbon black-reinforced modified fluororubber composition with low compression set, characterized in that, The components include the following parts by weight: 100 parts by weight of fluororubber; 10-30 parts by weight of silica; 2-15 parts by weight of carbon black; 1-3 parts by weight of vulcanizing agent; Accelerator 1-3 parts by weight; 1-3 parts by weight of release agent; The carbon black is N990 carbon black.

2. The composition according to claim 1, characterized in that, The components include the following parts by weight: 100 parts by weight of fluororubber; 25 parts by weight of silica; 2 parts by weight of carbon black; Accelerator 2 parts by weight; 2 parts by weight of vulcanizing agent; 1 part by weight of release agent.

3. The composition according to claim 1, characterized in that, The fluororubber is a peroxide-based fluororubber and / or a triazine-based fluororubber.

4. The composition according to claim 1, characterized in that, The release agent is struktol WS280 and / or struktol HT290.

5. The composition according to claim 1, characterized in that, The silica is hydrophobically modified silica and / or hydrophilically modified silica.

6. The composition according to claim 5, characterized in that, The weight ratio of the silica to the carbon black is (1.5-15):

1.

7. The composition according to claim 1, characterized in that, The accelerator is at least one of BPP, TAIC, and BTPPC.

8. The composition according to claim 1, characterized in that, The vulcanizing agent is at least one of bis(2,5-diphenyltriazine) tetrabutylammonium salt and BOAP.

9. A method for preparing the composition according to any one of claims 1-8, characterized in that, Includes the following steps: (1) Weigh the raw materials according to the formula requirements; (2) Add the raw materials from step (1) into a two-roll mill and mix them at a temperature of 35-75℃ until they are uniformly mixed to obtain a compound. (3) The compound obtained in step (2) is vulcanized in a vulcanizing machine at a vulcanization temperature of [temperature missing]. 155-190℃, vulcanization time is 8-12 minutes; (4) Place the material obtained by vulcanization in step (3) in a blower oven for two-stage vulcanization. The vulcanization temperature is 185-215℃ and the vulcanization time is 24h.

10. The preparation method according to claim 9, characterized in that, The initial refining temperature in step (2) is 50℃; In step (3), the vulcanization temperature is 170℃ and the vulcanization time is 10min; In step (4), the second stage vulcanization temperature is 200℃.

Citation Information

Patent Citations

  • Fluororubber for vacuum drying tank, and preparation method thereof

    CN110229446A